A carbonized polymer dot (CPD) nanosensor for trace water detection with a wide detection range. (December 2021) - Huo, Zepeng; Xu, Weiqing; Wang, Zizhun; Xu, Shuping
Abstract: Water plays an essential role in life activities, but in some scenes, water is impurity. Herein, we developed a fluorescent nanoprobe for tracing water content based on the carbonized polymer dot (CPD) prepared by ethylenediamine and catechol via the one-pot hydrothermal method. This carbon dot shows different responses in different organic solvents due to its abundant surface functional group controlled by hydrogen bonds. This nanoprobe exhibits excellent detection performance for the water content in various organic solvents, especially in 1, 4-dioxane. The limit of detection (LOD) of 0.0460 vol% and relative standard deviation (RSD) of 0.198% in 0.1 vol% water content (n = 3) were obtained by this analytical method. More importantly, this CPD-based fluorescent analytical method presents the broadest detection range (0.0–100.0 vol%) in tracing water in heavy water compared with other probes, and shows good repeatability (RSD = 2.25%, 5.0 vol% water content, n = 3) and low LOD (5.51 vol%). This study shows a new perspective for real-time monitoring water content and expands the applications of carbon materials in analytical fields. Graphical abstract: We successfully developed a novel ultrasensitive fluorescent probe based on carbonized polymer dot (CPD) for water content detection in many environments (D2 O and organic solvents). Image 1 Highlights: The nanoprobe can detect the water content in a variety of organic solvents. This nanoprobe can be applied for detecting water content in heavy water, which is scarcely reported. The sensing mechanism of this nanoprobe was studied.